Memory as a Hologram: An Analysis of Learning and Recall. - Franklin, Donald R. J.; Mewhort, D. J. K. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2015)
We present a holographic theory of human memory. According to the theory, a subject's vocabulary resides in a dynamic distributed representation—a hologram. Studying or recalling a word alters both the existing representation of that word in the hologram and all words associated with it. Recall is always prompted by a recall cue (either a start instruction or the word just recalled). Order of report is a joint function of the item and associative information residing in the hologram at the time the report is made. We apply the model to archival data involving simple free recall, learning in multitrial free recall, simple serial recall, and learning in multitrial serial recall. The model captures accuracy and order of report in both free and serial recall. It also captures learning and subjective organisation in multitrial free recall. We offer the model as an alternative to the short- and long-term account of memory postulated in the modal model.